Trichotillomania and Non-Epileptic Seizures as Sleep-Related Dissociative Phenomena - Angulo-Franco, Melina (J Clin Sleep Med, 2015)
The occurrence of non-epileptic seizures (NES) and trichotillomania during sleep is rare. We describe the case of an adult woman with a personal history of childhood maltreatment and psychiatric morbidity (major depression, trichotillomania, and conversion disorder), who was referred to the sleep unit because of nocturnal hair-pulling and psychomotor agitation during sleep. An all-night PSG recording with audiovisual monitoring documented seven episodes of trichotillomania and one NES, all of which arose from unequivocal wakefulness. Improvement of nocturnal behaviors was observed after long-term psychotherapy. This case illustrates that nocturnal trichotillomania and NES may be symptoms of a sleep-related dissociative disorder. CITATION: Angulo-Franco M, Bush-Martínez A, Nenclares-Portocarrero A, Jiménez-Genchi A. Trichotillomania and non-epileptic seizures as sleep-related dissociative phenomena. J Clin Sleep Med 2015;11(3):271–273.